The Australian species of Iphidozercon (Acari: Ascidae) - Gwiazdowicz, D. J.; Halliday, R. B. (Zootaxa, 2008)
The genus Iphidozercon Berlese (Acari: Ascidae) is reviewed. The genus is characterised mainly by a holodorsal shield without lateral incisions; the vertex of the dorsal shield bent sharply downward to conceal setae j1 from above; and the anterior ends of the peritremes bent sharply posteroventrally. Three new species are described from rainforest leaf litter in eastern Australia - I. australis sp. nov., I. foveatus sp. nov., and I. walteri sp. nov. The genus now includes eight species from Europe, the Middle East, Russia, North America, Australia and New Caledonia. A key to the known species worldwide is provided.